Cultural heritage enhancement for tourism - Nachouane, Nour Eddine (2019)
This paper presents some of the results of a Ph.D. thesis on Tourism Studies that presents a proposal for the enhancement of the cultural heritage at the Dar Debbagh tanneries in Marrakesh. The project proposes the creation of an interpretation center devoted to tanners and the processing of leather. Following the principles of heritage interpretation, we analyze the assets that can contribute to make these tanneries a heritage resource and a quality destination for cultural tourism.